An empirical test of the performance of intelligence and the prospects for organizational reforms. Issue 1 (2nd January 2018) - Grady, Kristopher
ABSTRACT: The occurrence of strategic surprises has led to the development of organizational reforms intended to prevent future intelligence failures. The limited effectiveness of such reforms conforms to a perspective that holds intelligence to be beset by inherent difficulties, such as ambiguous information, enemy deception, and human psychology, which make recurring intelligence failures inevitable. If this perspective is correct, then all functions of intelligence should be distinctly unreliable regardless of implemented reforms. I test this perspective through a comparison of the performance of military capabilities and tactical intelligence capabilities, in terms of their influence on battlefield outcomes. While tactical intelligence is susceptible to the inherent difficulties common to all functions of intelligence, it is less susceptible to the bureaucratic difficulties that most reforms, aimed at preventing strategic intelligence failures, are intended to address. I find that relatively strong tactical intelligence capabilities significantly improve battlefield effectiveness. However, the improvement associated with tactical intelligence capabilities is also significantly more inconsistent when compared to the corresponding improvement associated with military capabilities. Even when evaluating a function of intelligence less susceptible to bureaucratic difficulties, intelligence is still distinctly inconsistent in performance, suggesting that organizational reforms have only a limited ability to prevent future intelligence failures.